Severe Hepatitis in Pediatric Coronavirus Disease 2019. Issue 5 (May 2022) - Antala, Swati; Diamond, Tamir; Kociolek, Larry K.; Shah, Amit A.; Chapin, Catherine A.
Abstract : ABSTRACT: Hepatic involvement in coronavirus disease 2019 (COVID-19) is typically characterized as mild hepatitis with preserved synthetic function in children. Severe hepatitis is a rare complication of COVID-19 infection that has not been extensively described in the pediatric population. We report a case series of four previously healthy children who presented with significant hepatitis as the primary manifestation of COVID-19 infection. Two of these patients met criteria for acute liver failure. None of the patients had respiratory symptoms. One patient was found to have complement dysfunction resulting in microangiopathic features and was treated successfully with eculizumab. This case is in line with adult post-mortem data showing that more severe cases of hepatic dysfunction secondary to COVID-19 infection may be associated with complement activation and microangiopathic features. Liver function should be evaluated in cases of severe COVID-19, and severe acute respiratory syndrome coronavirus 2 infection should be considered as a cause of acute severe hepatitis even in patients without significant respiratory or other systemic symptoms.